A GYSEV Cargo ZRT. Logisztikai Központ technológiai folyamatai és fejlesztési lehetőségei - Pető Dániel Tibor (2016)
Nowadays logistic service centers have taken place. The main reason for it is the process which is popular among companies. They outsource the most of the logistic processes. GYSEV CARGO Inc. has a significant role in this field. In this paper, I presented my experiences of my internship. I chose this topic because of this internship. During the time spent there I had the opportunity to get to know all the processes which are necessary for an important logistic service center like the GYSEV CARGO Inc. Thereby, I could get a more accurate picture of the company’s current situation, field of action, as well the effectiveness of its processes. In the first part of my thesis I try to give an overall picture about the enterprise. I present its history in the beginning, its organisational structure, its services and the technologies used by the company. After that I focus on the main processes and procedures used in the GYSEV CARGO Inc. Then I represent the combinant and its services, functions and the company named HCCR Sopron‘s connection to this terminal. After that I list the IT systems used by the enterprise. I introduce that, which softwares can be used for the different tasks and what is their importance. During my internship I had the chance to gain information about the storage processes and their technologies used by the logistic service center, which are introduced as well. I also had the opportunity to get an accurate picture about the company’s complain handling, RMA, billing and marketing pocesses. In the fourth part of my thesis I explain my remarks more deeply about the company’s operation and the development opportunities for them. The development opportunities suggested by me point to help the working processes and make them faster and easier. The main essence of my thesis is to present why the logistic service center is so important in the everyday life.